2021
DOI: 10.3389/fonc.2021.708039
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Anti-PCSK9 Antibody Levels with Favorable Postoperative Prognosis in Esophageal Cancer

Abstract: BackgroundEsophageal cancer often appears as postoperative metastasis or recurrence after radical surgery. Although we had previously reported that serum programmed cell death ligand 1 (PD-L1) level correlated with the prognosis of esophageal cancer, further novel biomarkers are required for more precise prediction of the prognosis. Proprotein convertase subtilisin/kexin type 9 (PCSK9) is associated with the cholesterol metabolism. But there was no report of relationship between serum PCSK9 antibody and cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Third, the cases in this study were not surgically resected, so we could not analyze tumor tissues immunohistochemically. Serum autoantibodies are usually associated with TAA expression in tumor tissue ( 32 , 33 ). Similar to serum autoantibodies, Sui1, RalA, and p53 are reported to have higher expression rates in HCC than in normal liver, CH, or LC, as revealed through immunohistochemical studies ( 21 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the cases in this study were not surgically resected, so we could not analyze tumor tissues immunohistochemically. Serum autoantibodies are usually associated with TAA expression in tumor tissue ( 32 , 33 ). Similar to serum autoantibodies, Sui1, RalA, and p53 are reported to have higher expression rates in HCC than in normal liver, CH, or LC, as revealed through immunohistochemical studies ( 21 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PD-L1 expression was an independent protective factor for RFS. Most studies have shown that the high expression of PD-L1 is associated with poor prognosis because PD-L1 negatively regulated the anti-tumor response of T cells (31,32). On the contrary, in some malignant tumors, the high expression of PD-L1 was found to be associated with a good prognosis (33).…”
Section: Discussionmentioning
confidence: 99%
“…To construct the glutathione- S -transferase (GST)-fused protein expression plasmids, the cDNA sequences were recombined into the pGEX-4T vector (GE Healthcare Life Sciences, Pittsburgh, PA, USA) as previously described ( 32 , 35 , 37 ). The pBluescript plasmids associated with the cDNA inserts were digested with the restriction endonucleases Eco RI and Xho I and detached by agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%